The gender pay gap across countries: A human capital approach - Solomon W. Polachek; Jun Xiang (Luxembourg Income Study (LIS), 2015)
The gender wage gap varies across countries. For example, among OECD nations women in Australia, Belgium, Italy and Sweden earn 80% as much as males, whereas in Austria, Canada and Japan women earn about 60%. Current studies examining cross-country differences focus on the impact of labor market institutions such as minimum wage laws and nationwide collective bargaining. However, these studies neglect labor market institutions that affect women's lifetime work behavior - a factor crucially important in gender wage gap studies that employ individual data. This paper explicitly concentrates on labor market institutions that are related to female lifetime work that affect the gender wage gap across countries. Using ISSP (International Social Survey Programme), LIS (Luxembourg Income Study) and OECD wage data for 35 countries covering 1970-2002, we show that the gender pay gap is positively associated with the fertility rate, positively associated with the husband-wife age gap at first marriage, and positively related to the top marginal tax rate, all factors which negatively affect women's lifetime labor force participation. In addition, we show that collective bargaining, as found in previous studies, is negatively associated with the gender pay gap.
Keywords: 330